Growth, tolerance and safety outcomes with use of an extensively hydrolyzed casein-based formula in infants with cow's milk protein allergy - Kansu, Aydan; Urganci, Nafiye; Bukulmez, Aysegul; Kutluk, Gunsel; Taskin, Didem Gulcu; Keskin, Lutfiye Sahin; Erdogan, Simge (Frontiers Media Sa, 2023)
ObjectiveTo evaluate growth, tolerance and safety outcomes with use of an extensively hydrolyzed casein-based formula (eHCF) in infants with cow's milk protein allergy (CMPA). MethodsA total of 226 infants (mean & PLUSMN; SD age: 106.5 & PLUSMN; 39.5 days, 52.7% were girls) with CMPA who received eHCF comprising at least half of the daily dietary intake were included. Data on anthropometrics [weight for age (WFA), length for age (LFA) and weight for length (WFL) z-scores] were recorded at baseline (visit 1), while data on infant feeding and stool records, anthropometrics and Infant Feeding and Stool Patterns and Formula Satisfaction Questionnaires were recorded at visit 2 (on Days 15 & PLUSMN; 5) and visit 3 (on Days 30 & PLUSMN; 5). ResultsFrom baseline to visit 2 and visit 3, WFA z-scores (from -0.60 & PLUSMN; 1.13 to -0.54 & PLUSMN; 1.09 at visit 2, and to -0.44 & PLUSMN; 1.05 at visit 3, p < 0.001) and WFL z-scores (from -0.80 & PLUSMN; 1.30 to -0.71 & PLUSMN; 1.22 at visit 2, and to -0.64 & PLUSMN; 1.13 at visit 3, p = 0.002) were significantly increased. At least half of infants never experienced irritability or feeding refusal (55.7%) and spit-up after feeding (50.2%). The majority of mothers were satisfied with the study formula (93.2%), and wished to continue using it (92.2%). ConclusionsIn conclusion, eHCF was well-accepted and tolerated by an intended use population of infants & LE; 6 months of age with CMPA and enabled adequate volume consumption and improved growth indices within 30 days of utilization alongside a favorable gastrointestinal tolerance and a high level of parental satisfaction.
Keywords: cow's milk protein allergy; extensively hydrolyzed casein-based formula; growth indices; gastrointestinal intolerance; stool patterns; parental satisfaction